ANALISIS EFEKTIFITAS METODE PENGELOMPOKAN SAMPAH TERHADAP PENCEMARAN AIR SUNGAI DI KAMPUNG SARWANDORI - Rahanra, Roy Marthen; Aly, Muhamad Iksan B; Sinaga, Yeniwati; Fakaubun, Susanti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
The condition of the final disposal site (TPA) in Sarwandori village is very worrying for the residents and the surrounding environment. Public Health Conditions in Sarwandori village are experiencing various types of diseases, one of which is diarrhea. Starting from 2022-2024, there will be an increase in diarrheal diseases and an outbreak of the green fly Lucilia sericata. This research uses descriptive analytical methods. The aim of this research is to find out what impacts are felt by the community in Sarwandori village, such as the number of flies, river water pollution and plastic waste strewn on public roads. The research results show that the increase in disease is due to improper waste processing, there is no grouping or clustering of types of waste, and waste filtering (Trasering) has not been carried out by the environmental service. Other supporting data relating to the level of water pollution caused by seepage at the Final Disposal Site in the Yapen Islands Regency. If waste is grouped according to its type and disposed of according to the final waste disposal site, the water in the river will not be polluted by waste and disease-carrying flies will not breed and bring disease to the wider community. Good handling will produce good things too.